Rhinosinusitis: clinical-based phenotyping. - Ciprandi, Giorgio; Passali, Desiderio; Bellussi, Luisa Maria; Passali, Francesco Maria (Acta Biomedica Atenei Parmensis, 2022)
Rhinosinusitis (RS) is a common disease and is currently classified into two main types: acute RS (ARS) and chronic RS (CRS), which in turn includes CRS with or without nasal polyps. Different guidelines consider this classification. However, in clinical practice, other phenotypes exist. The current article would propose new clinical-based phenotyping of RS, including the following clinical phenotypes: simple catarrhal RS, Acute RS, acute bacterial RS, severe (complicated) acute RS, chronic RS, and recurrent chronic RS. Treatment strategy should be tailored considering the clinical phenotype and could include phytomedicines, intranasal non-pharmacological remedies, and local bacteriotherapy. In conclusion, RS requires thorough diagnostic work-up, and the therapeutic approach should be mainly based on appropriate management.